Composition of pseudodifferential operators associated with fractional Hankel–Clifford integral transformations. Issue 8 (2nd August 2016) - Prasad, Akhilesh; Kumar, Praveen
Abstract : Two versions of pseudodifferential operators (pdo) involving fractional powers Hankel–Clifford integral transformations are defined. The composition of first and second fractional pdo is defined. We show that the pdo and composition of pdo are bounded in a certain Sobolev-type space associated with the fractional powers of Hankel–Clifford integral transformations. Some special cases are also discussed.